2021
DOI: 10.3389/fpls.2020.545453
|View full text |Cite
|
Sign up to set email alerts
|

Role of Exogenous and Endogenous Hydrogen Sulfide (H2S) on Functional Traits of Plants Under Heavy Metal Stresses: A Recent Perspective

Abstract: Improving growth and productivity of plants that are vulnerable to environmental stresses, such as heavy metals, is of significant importance for meeting global food and energy demands. Because heavy metal toxicity not only causes impaired plant growth, it has also posed many concerns related to human well-being, so mitigation of heavy metal pollution is a necessary priority for a cleaner environment and healthier world. Hydrogen sulfide (H2S), a gaseous signaling molecule, is involved in metal-related oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 127 publications
(128 reference statements)
0
19
0
Order By: Relevance
“…The same findings were also documented by Opeolu et al (2010), they also demonstrated that the number of branches per tomato plant was reduced with increased heavy metal contamination of the soil. It has been suggested that reduction in plant growth and biomass may be due to heavy metal accumulation in the plant system, which disturbs biochemical and physiological activities and eventually leads to a reduction in growth and yield (Arif et al, 2021; Singh & Agarwal, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The same findings were also documented by Opeolu et al (2010), they also demonstrated that the number of branches per tomato plant was reduced with increased heavy metal contamination of the soil. It has been suggested that reduction in plant growth and biomass may be due to heavy metal accumulation in the plant system, which disturbs biochemical and physiological activities and eventually leads to a reduction in growth and yield (Arif et al, 2021; Singh & Agarwal, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative damage caused by heavy metals can be counteracted by maintaining redox homeostasis and levels of antioxidant enzymes (Gautam et al 2020;Raza et al 2021b). H 2 S, as a vital gaseous molecule, interacts with other molecules to reduce abiotic stresses, including heavy metal stress (Arif et al 2020;Huang et al 2021;Liu & Xue 2021). The tolerance to abiotic stresses, such as heavy metals in plants, can be boosted by H 2 S addition, regulating the transport of metal ions (Huang et al 2021;Liu & Xue, 2021).…”
Section: Heavy Metalsmentioning
confidence: 99%
“…hydrogen sulphide (H 2 S) and plant growth regulators (PGR) like salicylic acid (SA), to Cd stressed plants has received attention from researchers worldwide (Wang et al 2019;Luo et al 2020). To cope up with heavy metals, sulphur-induced defence mechanisms are among the most important strategies adopted by plants (Keyster et al 2020;Arif et al 2021). Hydrogen sulphide (H 2 S), a sulphurcontaining compound, has manifold functions in regulating key plant metabolic processes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2020; Arif et al . 2021). Hydrogen sulphide (H 2 S), a sulphur‐containing compound, has manifold functions in regulating key plant metabolic processes, e.g .…”
Section: Introductionmentioning
confidence: 99%